DEVELOPMENT OF THE COGNITIVE ASPECT OF CREATIVITY IN ADOLESCENTS THROUGH GROUP PSYCHOLOGICAL TRAINING - Liashch, Oksana; Yatsіuk, Mariia (Personality and environmental issues, 2024)
The study addresses the problem of developing creativity in adolescence as a crucial factor in modern education and personal growth. The relevance of the research is determined by the reform of the educational system in Ukraine, which emphasizes the importance of innovative thinking, flexibility, and the ability to find non-standard solutions in professional and social activities. Creativity is conceptualized as an integrative personal characteristic that enables the overcoming of stereotypes, the transformation of reality, and the generation of original ideas. Particular attention is paid to the cognitive component of creativity, which includes divergent thinking, originality, and the ability to restructure cognitive barriers.The theoretical foundation of the study combines a systemic approach with well-known psychological theories: Erikson’s concept of psychosocial development, V.O. Molyako’s concept of personality creativity, Torrance’s structural-dynamic theory of intelligence, and the theories of creative cognition by R.A. Finke, T.B. Ward, and S.M. Smith. Based on this framework, the purpose of the article is to theoretically and experimentally justify the use of group psychological training as an effective tool for the development of the cognitive aspect of creativity in youth.The methodological base included a formative experiment with 30 participants (15 in the experimental group and 15 in the control group), a specially designed training program, and a set of diagnostic tools: the Self-Assessment Scale of Innovative Qualities of Personality (Lebedeva, Tatarko), the Thinking and Creativity Type Questionnaire (Bruner, adapted by Rezapkina), and the Analytic-Holistic Scale (Choi, Koo, Choi). The training program was structured into three modules:  self-reflection and value-based self-attitude, overcoming barriers to creativity, and creative self-realization.The results demonstrate that group psychological training leads to statistically significant improvements in creative thinking, innovative potential, problem-solving abilities, and holistic cognitive processing. Participants of the experimental group reported increased confidence in creative expression, greater openness to novelty, and stronger motivation for self-realization. Importantly, group dynamics served as the main catalyst of change, providing a safe space for experimentation, social reinforcement, and mutual learning.The findings confirm that group psychological training is a highly effective method of developing the cognitive component of creativity in adolescence. It not only strengthens individual skills but also transforms the very style of thinking toward greater flexibility, originality, and openness to experience, thereby contributing to both personal and social development of youth.